Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1074/jbc.m200335200
|View full text |Cite
|
Sign up to set email alerts
|

Cellubrevin Alterations and Mycobacterium tuberculosis Phagosome Maturation Arrest

Abstract: The intracellular trafficking processes controlling phagosomal maturation remain to be fully delineated. Mycobacterium tuberculosis var. bovis BCG, an organism that causes phagosomal maturation arrest, has emerged as a tool for dissection of critical phagosome biogenesis events. In this work, we report that cellubrevin, a v-SNARE functioning in endosomal recycling and implicated in endosomal interactions with post-Golgi compartments, plays a role in phagosomal maturation and that it is altered on mycobacterial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 72 publications
3
34
0
1
Order By: Relevance
“…The ATPase NSF, together with soluble NSF attachment protein, is required in a broad range of vesicular docking and fusion events (43), and NSF was recently shown on M. bovis BCG phagosomes in J774 M-like cells (24,32). Consistent with these results, the ATPase NSF was continuously retained on the phagosome membrane in Ms, but the mycobacterial vacuoles in DCs were deficient of this marker (Fig.…”
Section: Tuberculosis Vacuoles Have No Access To the Biosynthetic supporting
confidence: 78%
See 1 more Smart Citation
“…The ATPase NSF, together with soluble NSF attachment protein, is required in a broad range of vesicular docking and fusion events (43), and NSF was recently shown on M. bovis BCG phagosomes in J774 M-like cells (24,32). Consistent with these results, the ATPase NSF was continuously retained on the phagosome membrane in Ms, but the mycobacterial vacuoles in DCs were deficient of this marker (Fig.…”
Section: Tuberculosis Vacuoles Have No Access To the Biosynthetic supporting
confidence: 78%
“…Thus, despite its limited fusogenicity towards organelles of the deep endocytic pathway, the mycobacterial phagosome appears to be very dynamic indeed. This feature correlates with the continuous presence of various fusion and docking factors, such as the ATPase N-ethylmaleimide-sensitive factor (NSF), onto the phagosomal membrane, whereas these factors are rapidly lost by phagolysosomes containing inert particles (24,32).…”
mentioning
confidence: 99%
“…Within the last decade, significant advances have been made in our understanding of Mtb-induced alterations in MP signal transduction pathways that may contribute to the organism's intracellular persistence. These include inhibition of phagosomal localization of the vacuolar H 烯 /ATPase that normally acidifies the phagolysosome (3), alterations of regulatory GTPases of the Rab family and its effector early endosomal Ag 1 (4,5), and modulation of the vesicular soluble N-ethylmaleimide attachment protein receptor cellubrevin (6). In these studies, comparisons between live and killed Mtb have provided valuable information and confirmed that inhibition of MP signaling is restricted to live bacilli.…”
Section: One-third Of the World's Population Is Infected Withmentioning
confidence: 97%
“…Consistently, several SNAREs, including VAMP3, syntaxin 4 and syntaxin 13, are recruited to the nascent phagocytic cup to mediate the membrane fusion events involved in exocytosis (Bajno et al, 2000;Collins et al, 2002;Fratti et al, 2002;Murray et al, 2005). Similar to Syt V , intact lipid microdomains are required for the recruitment of syntaxin 4 and VAMP3 to phagosomes (Kay et al, 2006).…”
Section: Discussionmentioning
confidence: 78%